Microtubule assembly and pole coalescence: early steps in Caenorhabditis elegans oocyte meiosis I spindle assembly - Chuang, Chien-Hui (Biol Open, 2020)
How oocytes assemble bipolar meiotic spindles in the absence of centrosomes as microtubule organizing centers remains poorly understood. We have used live cell imaging in Caenorhabditis elegans to investigate requirements for the nuclear lamina and for conserved regulators of microtubule dynamics during oocyte meiosis I spindle assembly, assessing these requirements with respect to recently identified spindle assembly steps. We show that the nuclear lamina is required for microtubule bundles to form a peripheral cage-like structure that appears shortly after oocyte nuclear envelope breakdown and surrounds the oocyte chromosomes, although bipolar spindles still assembled in its absence. Although two conserved regulators of microtubule nucleation, RAN-1 and γ-tubulin, are not required for bipolar spindle assembly, both contribute to normal levels of spindle-associated microtubules and spindle assembly dynamics. Finally, the XMAP215 ortholog ZYG-9 and the nearly identical minus-end directed kinesins KLP-15/16 are required for proper assembly of the early cage-like structure of microtubule bundles, and for early spindle pole foci to coalesce into a bipolar structure. Our results provide a framework for assigning molecular mechanisms to recently described steps in C. elegans oocyte meiosis I spindle assembly.